Myxobolus percarinae sp. n. (Myxosporidia) — новый вид слизистых споровиков от перкарины понтической (Percarina demidoffi) - Исков, М.П.; Каратаев, А.К. (Вестник зоологии, 1982)
A new Myxosporidian species, Myxobolus percarinae sp. nov., have been tound in Percarina demidojii specimens collected in the Dnieper estuary. Spores (vegetative stages not y e tfound) elongate-ovate, w i t hslightly narrowed frontal end. Polar capsules pyriform, of equal size, their excretory tubules with no crossings. The spores a r e спагасте- rized by very wide(1.2-1.5 um) sutureridge. Sporal dimensions (in u m ) :length - 10.8-13.0, width - 7.2-9.6, thickness - 6.8-7.2; polarcapsules length- 3.6-4.8,diameter - 2.0-2.4, nematocyst filament length - ca. 40. Type material is deposited ni the collection of the Institute of Zoology, Ukrainian SSR Academy of Sciences.